Are Risk Aversion and Impatience Related to Cognitive Ability? - Dohmen, Thomas; Falk, Armin; Huffman, David; Sunde, Uwe (American Economic Review, 2010)
This paper investigates whether there is a link between cognitive ability, risk aversion, and impatience, using a representative sample of roughly 1,000 German adults. Subjects participate in choice experiments with monetary incentives measuring risk aversion, and impatience over an annual horizon, and conduct two different, widely used, tests of cognitive ability. We find that lower cognitive ability is associated with greater risk aversion, and more pronounced impatience. These relationships are significant, and robust to controlling for personal characteristics, education, income, and measures of credit constraints. We perform a series of additional robustness checks, which help rule out other possible confounds.